Case report: A novel surgical technique for rapid valve-in-ring implantation into the native aortic annulus during left ventricular assist device implantation - Pya, Yuriy; Mussayev, Abdurashid; Novikova, Svetlana; Bekbossynova, Makhabbat; Alimbayev, Serik; Khissamutdinov, Nail; Kapyshev, Timur; Kuanyshbek, Aidyn; Lesbekov, Timur (Frontiers in Cardiovascular Medicine, 2023)
Left ventricular assist device (LVAD), a mechanical pump, has promising use in patients with heart failure. Aortic valve insufficiency is one of the contraindications for LVAD implantation in patients with end-stage heart failure. The reason for this may be the decreasing efficiency of mechanical support and subsequent right ventricular failure. Here, we present the first ever report of the novel technique of transcatheter aortic valve replacement (TAVR) in valve in ring (ViR) assisted with LVAD implantation for the treatment of a 60-year-old male suffering from dilated cardiomyopathy and pure aortic insufficiency who needed LVAD and a new aortic bioprosthesis. Myval transcatheter heart valve (THV) was implanted into a previously sewn annulus ring into the aortic root via transaortic access route. Next HeartMate 3TM LVAD was implanted. This novel and feasible option reduces the overall time of surgeries, avoids risk of redo sternotomy, reduces length of surgery and complications associated with cross clamping.